Atypical naevus spilus: detection by in vivo confocal microscopy. (July 2014) - Laing, M. E.; Coates, E.; Jopp‐McKay, A.; Scolyer, R. A.; Guitera, P.
Summary Naevus spilus (NS) is a naevoid disorder characterized by hyperpigmented macules or papules scattered over a café‐au‐lait macule. Such café‐au‐lait macules are often present at birth, and the darker pigmented speckles of NS slowly increase in number and size over a period of several years. NS can therefore be difficult to evaluate clinically for the development of melanoma. In vivo confocal microscopy (IVCM) is a novel method that allows examination at cellular resolution of cutaneous lesions in vivo. IVCM has been shown to have twice the specificity of dermoscopy for the diagnosis of melanoma, with comparable sensitivity. It has been shown to be useful in the detection and grading of dysplastic naevi, which are recognized precursors of melanoma in some cases. In this report, we highlight that IVCM can also be used as a tool complementary to dermoscopy to identify areas of dynamic change in clinically and dermoscopically equivocal lesions. IVCM may thereby assist in the early detection of melanocytic atypia and melanoma arising in NS, in turn leading to excision of melanoma at an early stage, which is associated with a favourable outcome. We also outline some of the difficulties encountered in confocal microscopy and histology when differentiating melanoma from dysplastic naevi.